Grounds for establishing a professional self-governing body of driving instructors and driving license examiners under art. 17 sec. 1 of the Constitution of the Republic of Poland - Wilczyński, Karol (Studia Iuridica Toruniensia, 2021)
The subject of the article are the premises for establishing the professional self-government of driving instructors and driving licence examiners. In the opinion of instructors and examiners, their professions belong to the category of public trust professions. In the light of performed analysis, they do not have the constitutional features allowing to consider that at present the professional self-government (mentioned in Art. 17(1) of the Constitution of the Republic of Poland) constitutes the best form of their organization. This should not be excluded in the future, provided that the certain conditions are fulfilled.